DENOMINATIVE VARIATION IN THE TERMINOLOGY OF FAUNA AND FLORA: CULTURAL AND LINGUISTIC (A)SYMMETRIES - Martins, Sabrina de Cassia [UNESP] (Univ Federal Santa Catarina, Nucleo Traducao, 2018)
The present work approaches the denominative variation in Terminology. In this way, it has as object of study the specialized lexical units in Portuguese language formed by at least one of the following color names: black, white, yellow, blue, orange, gray, green, brown, red, pink, violet, purple and indigo. The comparative analysis of this vocabulary among Portuguese, English and Italian languages was conducted considering two sub-areas of Biology: Botany, specifically Angiosperms (Monocotyledons and Eudicotyledons), and Zoology, exclusively Vertebrates (fish, amphibians, reptiles, birds and mammals). It will be described in the next pages how common names are created in these tree languages.
Keywords: Terminology; Denominative variation; Fauna and flora; Color names